Development and Analysis of Wearable Textile Antenna (WTA) Design for ISM and HiperLAN Applications - Nurul Husna Mohd Rais (School of Computer and Communication Engineering, 2012)
The main scope of the research work presented in the thesis is to design and develop antennas using conductive textiles suitable for body area network.